Growth, Feed Utilization, Lipid Metabolism, and Metamorphosis of Bullfrog (Aquarana catesbeianus) Tadpoles Fed Diets With Different Lipid Levels - Juan Gao; Ling Wang; Jian Zhang; Kangle Lu; Kai Song; Xueshan Li; Chunxiao Zhang (Aquaculture Nutrition)
This study investigated the effect of dietary lipid levels on growth performance, lipid metabolism, antioxidant capacity, digestive enzyme activity, and metamorphosis rate of bullfrog (Aquarana catesbeianus) tadpoles. A total of six isonitrogenous diets were prepared, each containing 4.46% (L5), 6.95% (L7), 9.10% (L9), 10.90% (L11), 12.34% (L13), and 15.00% (L15) crude lipid content. The experimental diets were administered to triplicates of tadpoles (stage 25, 0.007 g) twice daily for 75 days with a daily feeding rate of 6.50% of their body weight. Weight gain (WG), specific growth rate (SGR), crude protein content of the whole body, apparent digestibility of dry matter and gross energy, intestinal lipase (LPS) capacity, lipoprotein lipase (LPL), and carnitine palmitoyltransferase-I (CPT-I) and contents of growth hormone (GH) and insulin-like growth factor-1 (IGF-1) in the liver, high-density lipoprotein cholesterol (HDL-C) content in the serum, and metamorphosis rate at stages 40 and 41 increased as the dietary lipid level increased from 4.46% to 12.34% and then decreased. As the dietary lipid level increased from 4.46% to 10.90%, the protein efficiency ratio (PER), protein deposition rate (PDR), lipid deposition rate (LDR), crude lipid content and gross energy of the whole body, apparent digestibility of the crude lipid, superoxide dismutase (SOD), catalase (CAT) activities in the liver, and the intestinal trypsin (TPS) activity all increased and then decreased. According to the second-order polynomial regression analysis of the WG and metamorphosis rate at stage 41 to the dietary lipid level, the ideal dietary lipid content for tadpoles was 11.08% and 10.72%, respectively. Overall, the appropriate dietary lipid level for bullfrog tadpoles was found to be 10.72%–11.08% of the diet.